(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Cultural relics are the carriers of history, storing the essence of Chinese culture for 5,000 years. Through the conservation and utilization of cultural relics, it can preserve historical memory, provide an important reference value for the historical research of Chinese civilization, and allow more people to understand Chinese culture. With the advent of the digital era, the Institute of Cultural Relics and Archaeology has introduced high technology in order to enhance the conservation and utilization of cultural relics. Based on this, this paper focuses on exploring the use of high technology to enhance the conservation and utilization of cultural relics. I hope to provide some help to the Institute of Cultural Relics and Archaeology of cultural relics regarding the protection and utilization of the cause.